Operationalizing the social-ecological systems framework in pond aquaculture. Issue 1 (March 2018) - Partelow, Stefan; Senff, Paula; Buhari, Nurliah; Schlüter, Achim
This study develops and applies an interdisciplinary and mixed method approach to operationalize the social-ecological systems (SES) framework in the context of aquaculture, the fastest growing food production sector worldwide. We apply this methodology to conduct a case study of community-based pond aquaculture on the island of Lombok, West Nusa Tenggara, Indonesia. This diagnostic approach demonstrates how sustainability challenges are interrelated at multiple levels through an analysis applying common-pool resource (CPR) and collective action theories. At the community level, qualitative data show how pond aquaculture systems can have CPR dilemmas, requiring communities to work together to solve them. We show how a provision dilemma manifests from the need to maintain common canal infrastructure to distribute water to private ponds. Asymmetric incentives to contribute exist because there are up and downstream users in the pond network, similar to some irrigation systems. Second, at the level of individual ponds, we developed indicators for the Resource System, Resource Unit, Governance and Actor tiers of the SES framework. Indicator data for each pond was measured and transformed into normalized quantitative scores to examine the relationships between social and ecological outcomes within and between ponds. We combine the results of our multi-level analysis to discuss the broader social-ecological relationships which link collective action challenges in managing common canal infrastructure with pond level outcomes and current government policies for advancing community development. We emphasize the need for increased knowledge and training on effective aquaculture practice as an underlying driver of current system conditions. This study raises many methodological challenges associated with designing empirically based SES research and building SES theory. We discuss challenges with integrating diverse data types, indicator selection and making normative assumptions about sustainability.